The Impact of Malnutrition on Infant Mortality Rate in Indonesia: A Spline Regression Approach - Muthahharah, Isma; Hidayat, Rahmat (Journal of Mathematics, Computations and Statistics, 2025)
The Infant Mortality Rate (IMR) in Indonesia is still an important index in assessing the quality of public health. One aspect that is thought to influence the high IMR is malnutrition. One of the objectives of this study is to analyze the relationship between malnutrition and IMR through a nonparametric spline regression approach. The data used in this study are secondary data obtained from the Central Statistics Agency in 2022 with the IMR variable as the dependent variable and the percentage of malnutrition as the independent variable. The spline regression model was chosen because it is able to capture the nonlinear relationship between the variables analyzed. Based on the research results that have been obtained, we can see that the best model is spline regression, namely by selecting three knot points, the coefficient of determination (R^2) value is 23,27%. However, this model still has limitations, such as violations of residual assumptions. Therefore, it is hoped that further research will add or select other variables that may be more relevant in order to improve the quality of the model.